2013
DOI: 10.1002/macp.201300669
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photovoltaic Characterization of Dithieno[3,2‐b:2′,3′‐d]thiophene‐Derived Narrow‐Bandgap Polymers

Abstract: Three novel dithieno[3,2‐b:2′,3′‐d]thiophene‐based low‐bandgap polymers are synthesized by a Suzuki–Miyaura coupling reaction or by direct arylation polycondensation. The polymers present a high molecular weight (26–32 kDa) and narrow polydiversity (1.3–1.7). With a highest occupied molecular orbital (HOMO) energy level around −5.20 eV, these polymers exhibit a narrow bandgap of 1.75–1.87 eV. All the polymers display strong absorption in the range of 350–700 nm. Bulk‐heterojunction (BHJ) solar cells are furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Kuwabara et al 39 reported that electron-deficient monomers were unreactive in palladium-catalyzed direct arylation reactions carried out in polar solvents such as N,N-dimethylacetamide. To overcome this, approaches such as increased reaction temperatures, longer reaction times or the addition of supporting ligands might be successful in improving the molecular weight, 26,27,29,38,39,46,48,55,58 but the multiple reactive protons on CPDT easily lead to the formation of insoluble branched polymers under harsh reaction conditions. To completely exploit the merits of direct arylation, careful design and consideration of the monomer structure is necessary to avoid the occurrence of side reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuwabara et al 39 reported that electron-deficient monomers were unreactive in palladium-catalyzed direct arylation reactions carried out in polar solvents such as N,N-dimethylacetamide. To overcome this, approaches such as increased reaction temperatures, longer reaction times or the addition of supporting ligands might be successful in improving the molecular weight, 26,27,29,38,39,46,48,55,58 but the multiple reactive protons on CPDT easily lead to the formation of insoluble branched polymers under harsh reaction conditions. To completely exploit the merits of direct arylation, careful design and consideration of the monomer structure is necessary to avoid the occurrence of side reactions.…”
Section: Resultsmentioning
confidence: 99%
“…[26][27][28][29]38,39,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] Recently, the application of directly arylated polymers to the preparation of OPVs has been investigated. 45,54,55 In this study, we report the synthesis and characterization of double acceptor copolymers, -(CPDT-TPD-CPDT-BT) n -, comprising TPD, BT and two CPDT units in the polymer-repeating unit (Figure 1). To compare the optical and electric properties of the analogous polymers and better understand the influence of BT and TPD in the polymers, a series of copolymers comprising CPDT-A-CPDT (A: acceptor = BT or TPD) and thiophene or bithiophene units has also been prepared (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The Fagnou conditions have been developed by Fagnou et al for the synthesis of small molecules via direct arylation in 2006 and then later adopted for the synthesis of conjugated polymers with little or no modifications . The conditions include rather simple, inexpensive, and bench‐stable reagents.…”
Section: Structural Defects In Darp Polymersmentioning
confidence: 99%
“…[8,16] The light-harvesting co-polymers described to date combine the thiazolothiazole moiety with such diverse (hetero)cyclic units as benzo[1,2-b:4,5-b′]dithiophene [52][53][54][55][56][57][58][59][60] (also with furan rings in the main chain [61] ), benzo[1,2-b:4,3-b′]dithiophene, [62] benzo[1,2-b:4,5-b′]difuran, [63] benzotrithiophene, [64] cyclopentadithiophene, [41,51,57] carbazole, [57,65,66] phenanthrocarbazole, [40] naphthalene, [67] indacenodithiophene, [68] indacenodibenzothiophene, [69] indacenodithienothiophene, [70] dibenzosilole, [57] dithienopyrrole, [57,71] dithienothiophene, [72] dithienosilole, [42,56,73,[74][75][76][77][78][79] dithienogermole, [80] indenofluorene and indolocarbazole, [81] thiophene, [82][83][84][85][86] bi(benzothiophene), …”
Section: Tztz-containing Polymersmentioning
confidence: 99%